1962
DOI: 10.2135/cropsci1962.0011183x000200020024x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Density Classification as a Selection Technique on Breeding Soybeans for Protein or Oil1

Abstract: PERCENTAGE protein and oil are important in evalu-•*• ating breeding lines of soybeans. The chemical method now used is costly, and if it were used on single plants grown at ordinary spacings, little or no seed would remain for planting. A reliable, low cost method for evaluating single plants for protein or oil content in a breeding program without destroying the seed for planting would have considerable value. The density of soybean oil is approximately 0.93 gram per cc. and the density of the non-oil portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1962
1962
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…The phenotypic association for seed density with protein and oil reported in this study are in close agreement with those reported by Hartwig and Collins (1962) for specific gravity with protein and oil. The correlations reported in this study are measurements of association of the mean oil and protein performance for a line with the mean seed density value.…”
Section: Interrelationship Of Characterssupporting
confidence: 91%
See 1 more Smart Citation
“…The phenotypic association for seed density with protein and oil reported in this study are in close agreement with those reported by Hartwig and Collins (1962) for specific gravity with protein and oil. The correlations reported in this study are measurements of association of the mean oil and protein performance for a line with the mean seed density value.…”
Section: Interrelationship Of Characterssupporting
confidence: 91%
“…In experiments with rye from 1951 to 1959, Hoogland (1961) found that the leaf number per plant was increased considerably using mass selection. Romero and Frey (1966) practiced mass selection for height in oats for four generations beginning water solutions with step-wise-increasing specific gravities were used by Hartwig and Collins (1962) to stratify a lot of soybean seed into specific gravity classifications. Those lots of seed having a high specific gravity classification had a protein percentage above the mean of the original lot, and the lots having low specific gravity classifica tion had an oil percentage above the mean of the original lot of seed.…”
Section: Artificial and Natural Mass Selectionmentioning
confidence: 99%
“…Burton, unpublished data, 1992). Because seed density has been used to evaluate seeds for protein content (Hartwig and Collins, 1962), it could potentially be used for indirect selection of protein content.…”
mentioning
confidence: 99%
“…In experiments with rye from 1951 to 1959, Hoogland (1961) found that the leaf number per plant was increased considerably using mass selection. Romero and Frey (1966) practiced mass selection for height in oats for four generations beginning water solutions with step-wise-increasing specific gravities were used by Hartwig and Collins (1962) to stratify a lot of soybean seed into specific gravity classifications. Those lots of seed having a high specific gravity classification had a protein percentage above the mean of the original lot, and the lots having low specific gravity classifica tion had an oil percentage above the mean of the original lot of seed.…”
Section: Artificial and Natural Mass Selectionmentioning
confidence: 99%